A Facile and Green Approach Toward Preparation of Nanocellular Poly(Butylene Succinate)/Hydroxyl‐Functionalized Graphene Composite Foam Induced by Nonisothermal Crystallization. Issue 4 (29th January 2020) - Zhou, Hongfu; Qu, Zhongjie; Yin, Dexian; Ye, Hong; Yu, Kejing; Wang, Xiangdong
Abstract : In this article, a facile and green strategy of nonisothermal crystallization induction was proposed to produce nanocellular biodegradable polymer composite foams, which was demonstrated by a composite system of poly(butylene succinate) (PBS) modified by hydroxyl‐functionalized graphene (HG) and chain extender. Nanocellular foams of chain extended PBS (CPBS) and CPBS/HG composite were prepared successfully with supercritical CO2 . Two significant phenomena about the preparation of nanobubbles in CPBS and CPBS/HG composite foams were found. One was that the nanobubbles generated at the temperature region of crystallization transition and the other was that chain extension played a critical function in the generation of nanobubbles. As the foaming temperature switched from 86 to 85°C, an interesting microbubble to nanobubble transition in CPBS and CPBS/HG foams was observed. Due to the generation of nanobubbles and the enhancement of volume expansion ratio, an excellent thermal insulation performance was achieved by CPBS/HG foams. J. VINYL ADDIT. TECHNOL., 26:461–474, 2020. © 2020 Society of Plastics Engineers